The Herschel–ATLAS data release 2, Paper I. Submillimeter and far-infrared images of the South and North Galactic Poles: the largest Herschel survey of the extragalactic sky - Smith, Matthew W.L.; Ibar, E.; Maddox, S.J.; Valiante, Elisabetta; Dunne, Loretta; Eales, S.; Dye, S.; Furlanetto, C.; Bourne, N.; Cigan, P.J.; Ivison, R.J.; Gomez, Haley; et al. (American Astronomical Society, 2017)
We present the largest submillimeter images that have been made of the extragalactic sky. The Herschel Astrophysical Terahertz Large Area Survey (H-ATLAS) is a survey of 660 deg2 with the PACS and SPIRE cameras in five photometric bands: 100, 160, 250, 350, and 500 μm. In this paper we present the images from our two largest fields, which account for ~75% of the survey. The first field is 180.1 deg2 in size, centered on the north Galactic pole (NGP), and the second is 317.6 deg2 in size, centered on the south Galactic pole. The NGP field serendipitously contains the Coma cluster. Over most (~80%) of the images, the pixel noise, including both instrumental noise and confusion noise, is approximately 3.6, and 3.5 mJy pix−1 at 100 and 160 μm, and 11.0, 11.1 and 12.3 mJy beam−1 at 250, 350 and 500 μm, respectively, but reaches lower values in some parts of the images. If a matched filter is applied to optimize point-source detection, our total 1σ map sensitivity is 5.7, 6.0, and 7.3 mJy at 250, 350, and 500 μm, respectively. We describe the results of an investigation of the noise properties of the images. We make the most precise estimate of confusion in SPIRE maps to date, finding values of 3.12 ± 0.07, 4.13 ± 0.02, and 4.45 ± 0.04 mJy beam−1 at 250, 350, and 500 μm in our un-convolved maps. For PACS we find an estimate of the confusion noise in our fast-parallel observations of 4.23 and 4.62 mJy beam−1 at 100 and 160 μm. Finally, we give recipes for using these images to carry out photometry, both for unresolved and extended sources.